PERSONAL BRANDING SEBAGAI EDUPRENEURSHIP DALAM MENINGKATKAN DAYA SAING MAHASISWA PENDIDIKAN BAHASA ARAB DI DUNIA KERJA - Mukmin Ridoan Simamora; Muhammad Jafar Shodiq; Lailatu Rohmah (Jurnal Pendidikan Ekonomi (JURKAMI), 2026)
In the era of globalization and increasingly competitive job markets, students are required not only to possess academic competence but also personal skills that enhance their competitiveness in the workforce. One crucial aspect that has gained attention in this context is personal branding. Students of the Arabic Language Education Study Program face unique challenges in building a strong professional image, particularly in confronting stereotypes of limited job prospects. This study aims to examine the role of personal branding in enhancing the employability of Arabic Language Education students through a literature review approach. The research method used is qualitative with a descriptive qualitative design, analyzing various scholarly sources such as journals, books, and relevant articles. The findings reveal that personal branding plays a significant role in shaping professional identity, boosting self-confidence, expanding professional networks, and enabling students to be recognized by both educational and non-educational industries. The use of professional social media platforms such as LinkedIn, Instagram, YouTube, professional blogs, and TikTok has proven effective as strategic tools for showcasing competencies, achievements, and expanding professional connections. The implications of this study highlight the need to integrate personal branding training into the curriculum and student self-development programs as a strategy to better prepare students for entering a competitive job market.